Influence of sodicity on growth, yield, quality and ionic composition of turmeric (Curcuma longa L.) - Garg, V K (Journal of Spices and Aromatic Crops, 2011)
The influence of sodicity on growth, yield and curcumin content of turmeric (Curcuma longa) grown in Typic Natrustalfs soil at Banthra, Lucknow (Uttar Pradesh) was studied. The experiments were laid out in a split plot design with five levels of soil exchangeable sodium percentage (10, 20, 30, 40 and 50) as main plot treatments and four varieties (Local BRS, KTS-1, Rajendra Sonia and Meducar) as sub-plot treatments with three replications. The results showed that emergence of rhizomes was marginally affected due to sodicity. However, an adverse effect of sodicity on number of tillers clump-1 rather than plant height and number of leaves was observed. The estimated fresh rhizome yield on sodic soil followed the order of Meducar (4.8 t ha-1) > Local BRS (4.4 t ha-1) > KTS-1 (4.29 t ha-1) > Rajendra Sonia (3.68 t ha-1). The highest cured rhizome yield (0.96 t ha-1) was obtained in Meducar followed by Local BRS > KTS-1 > Rajendra Sonia. The curcumin content was higher in Local BRS (9.6%) and Meducar (10.5%) than other genotypes grown in sodic soil. An accumulation of nutritionally adequate amount of potassium (K) and calcium (Ca) besides maintenance of greater K/Na (5.9) and Ca/Na (5.6) ratios in the foliage at ESP 20 indicated the potential of turmeric to withstand mild sodicity.